2021
DOI: 10.1038/s41467-021-26692-z
|View full text |Cite
|
Sign up to set email alerts
|

Global distribution, trends, and drivers of flash drought occurrence

Abstract: Flash drought is characterized by a period of rapid drought intensification with impacts on agriculture, water resources, ecosystems, and the human environment. Addressing these challenges requires a fundamental understanding of flash drought occurrence. This study identifies global hotspots for flash drought from 1980–2015 via anomalies in evaporative stress and the standardized evaporative stress ratio. Flash drought hotspots exist over Brazil, the Sahel, the Great Rift Valley, and India, with notable local … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
119
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 196 publications
(136 citation statements)
references
References 62 publications
(118 reference statements)
15
119
0
2
Order By: Relevance
“…SVDI was calculated with NLDAS and compared to PDSI, SPEI, and EDDI during a short-term “Flash Drought” event in central United States in 2003. This region was chosen due to the high frequency of Flash Drought events 55 , and the SVDI captures the rapid onset in the central Midwest in July 2003 and the rapid recovery. Similar results for the 2000, 2006 and 2007 summer Flash Drought events are shown in the supplementary materials: Figs.…”
Section: Discussionmentioning
confidence: 99%
“…SVDI was calculated with NLDAS and compared to PDSI, SPEI, and EDDI during a short-term “Flash Drought” event in central United States in 2003. This region was chosen due to the high frequency of Flash Drought events 55 , and the SVDI captures the rapid onset in the central Midwest in July 2003 and the rapid recovery. Similar results for the 2000, 2006 and 2007 summer Flash Drought events are shown in the supplementary materials: Figs.…”
Section: Discussionmentioning
confidence: 99%
“…By comparing two different flash drought definitions and using multiple datasets, the results from the study are expected to provide a broad and robust understanding of flash drought mechanisms and drivers globally. This is particularly important to highlight the advantages and limitations of the available flash drought definitions used by researchers and stakeholders (Christian, Basara, Otkin, & Hunt, 2019; Christian, Basara, Otkin, Hunt, et al., 2019; Christian et al., 2021; Mo & Lettenmaier, 2015, 2016; Otkin et al., 2018; L. Wang & Yuan, 2018). The new information gained in this study can be further extended to investigate the causal linkages of soil moisture memory length, vegetation fluxes, heatwaves and wildfires (Christian et al., 2020), and water use efficiency with FD characteristics across different ecosystems.…”
Section: Discussionmentioning
confidence: 99%
“…This methodology relies upon the concept of evaporative stress ratio (ESR (Anderson et al, 2007a(Anderson et al, , 2007bChristian et al, 2021), which is calculated based on the ratio between AET and PET as,…”
Section: Fd Sesr Detection Methodologymentioning
confidence: 99%
“…Recent studies based on the Palmer Drought Severity Index (PDSI) show that the severity of drought in some water-limited regions of the world, such as the west and southwest of the United States, has responded mainly to the increase in temperature over the last few years (Ault et al, 2016;Williams et al, 2015Williams et al, , 2020, which would emphasize the importance of AED in triggering recent drought events that could also affect the occurrence of flash droughts. For example, Christian et al (2021) suggested a significant increase in flash droughts in some regions, such as the Iberian Peninsula, Brazil, and the Sahel, associated with global warming. Other studies also reported an increase in flash drought frequency in China Wang et al, 2016;Yuan et al, 2019) and southern Africa (Yuan et al, 2018) linked to this process.…”
Section: Resultsmentioning
confidence: 99%